Epidemiology and Survival of Colorectal Cancer in Lebanon: A Sub-National Retrospective Analysis - Chatila, Rajaa (2021)
Background Scarce data exist about colorectal cancer (CRC) presentation and outcomes in Lebanon. The aim of this study is to describe the characteristics of Lebanese patients diagnosed with colorectal cancer, particularly the method of detection, age of onset, stage at presentation, treatment modalities, and survival. Methods This is a retrospective study of a cohort of patients with CRC, diagnosed between 2005 and 2010, admitted to 6 major university-affiliated medical centers in Lebanon. Results The total sample consisted of 586 patients (median age: 64 years; M:F ratio: 1.25). The most common presenting symptoms were changes in bowel habits, abdominal pain, and blood per rectum. Only 3% had been diagnosed by screening colonoscopy. Of the patients diagnosed with CRC younger than 50 years of age, 72.5% had a positive family history (P = .07). More than two-thirds of patients had an advanced stage of the disease III and IV at presentation. The Kaplan–Meier–estimated survival rate was 0%, 44.5%, 70.2%, and 78.5% for those with stage IV, III, II, and I, respectively (P = .0001), and did not vary by age nor gender of the patient. There was no differential in survival estimate for patients with stage II and III by number of chemotherapy cycles received. However, there was a significant difference in median survivorship for patients with metastatic stage IV disease; those who received less than or equal to 9 cycles had a median survivorship of 2 years (CI: 1.31–2.68) compared to 4 years (CI: 2.36–5.63) for those who received more than 9 cycles (P = .047). The cox regression showed while controlling for age and gender that patients diagnosed at stage IV had a hazard ratio of 8.81 (3.20–24.22) compared to those who were diagnosed at stage I (P = .047). Conclusions Lebanese patients affected by colorectal cancer tend to present with advanced disease stages, leading to poor prognosis and survival.